Determinants of Behavior and Proportion of Exclusive Breastfeeding at Tapung Health Center, Kampar Regency - Iin Rodearni; Zulfan Saam; Kamali Zaman; Jasrida Yunita; Novita Rany (Science Midwifery, 2022)
Breast milk is one of efforts to improve the mother and infant's health, one of which is reduce infant mortality rate (IMR). The prevalence of infants that receive the eclusive breastfeeding at The Tapung II public Health Center in 2020 was 57.1%. The purpose of this research is to know the determinant relationship of Exclusive Breastfeeding at The Tapung II Public health center in 2021. Type of this research is quantitative research observational with analytic cross sectional study. The population are Mothers who have babies aged 6-11 months. The sampling is non-probability sampling with consecutive sampling. The analysis used Chi Square and Multiple logistic regression with predictive model. The result of research is the proportion of infant who get exclusive breastfeeding is 43 people (45, grand mother's support and the early initiation of breast feeding) with exclusive breast feeding at The Tapung II Public Health Center. The recommending to health workers are increase the coverage of exclusive breast feeding through a health promotion strategy approach grand mother's support and the early initiation of breast feeding) with exclusive breast feeding at The Tapung II Public Health Center. The recommending to health workers are increase the coverage of exclusive breast feeding through a health promotion strategy approach